Temperature dependences of the Peclet number in sublimation processes of simple substances - Kravchenko, A.I.; Zhukov, A.I.; Datsenko, O.A. (Вопросы атомной науки и техники, 2022)
The results of calculating the Peclet number Ре = wr/(ρD) (where D is the diffusion coefficient; w is the evaporation rate of the substance; ρ is the density of the substance; r is the size factor) in sublimation processes of simple substances with high values of vapor pressure (≈ 1 mm Hg and above at the melting temperature): As, Gd, Tm, Lu, Cr, Yb, Sm, Mg, Ra, Ca, Sr, Ni, Co, Eu, Mn, Ba. It is shown that the nature of the temperature dependence Pe(T) is determined by the properties of the components of the sublimated system “base–impurity” (including the diffusion activation energy Q of impurity). For each substance for given Q and r, the dependence Pe(T) is monotonic. A decrease in the process temperature can improve the purification of a substance from one of several impurities, accompanied by deterioration in the purification from another impurity. Представлено результати обчислень числа Пекле Ре = wr/(ρD) (де D – коефіцієнт дифузії; w – швидкість випаровування речовини; ρ – щільність речовини; r – розмірний фактор) у процесах сублімації простих речовин з високими значеннями тиску пари (≈ 1 мм рт. ст. і вище при температурі плавлення): As, Gd, Tm, Lu, Cr, Yb, Sm, Mg, Ra, Ca, Sr, Ni, Co, Eu, Mn, Ba. Показано, що характер температурної залежності Ре(Т) визначається властивостями компонентів системи «основа–домішка» (включаючи енергію активації дифузії Q домішки). Для кожної речовини при заданих Q і r залежність Ре(Т) монотонна. Зниження температури процесу може покращувати очищення речовини від однієї з кількох домішок, супроводжуючись погіршенням очищення від іншої домішки. Представлены результаты вычислений числа Пекле Ре = wr/(ρD) (где D – коэффициент диффузии; w – скорость испарения вещества; ρ – плотность вещества; r – размерный фактор) в процессах сублимации простых веществ с высокими значениями давления пара (≈ 1 мм рт. ст. и выше при температуре плавления): As, Gd, Tm, Lu, Cr, Yb, Sm, Mg, Ra, Ca, Sr, Ni, Co, Eu, Mn, Ba. Показано, что характер температурной зависимости Ре(Т) определяется свойствами компонентов сублимируемой системы «основа–примесь» (включая энергию активации диффузии Q примеси). Для каждого вещества при заданных Q и r зависимость Ре(T) монотонна. Снижение температуры процесса может улучшать очистку вещества от одной из нескольких примесей, сопровождаясь ухудшением очистки от другой примеси.